Factorial validity of the Mental Toughness Questionnaire-48 - Perry, John L.; Clough, Peter J.; Crust, Lee; Earle, Keith; Nicholls, Adam R. (Personality And Individual Differences, 2013)
The purpose of this study was to assess the factorial validity of the Mental Toughness Questionnaire-48 (Clough, Earle, & Sewell, 2002). In total, 8207 participants (male n= 4019, female n= 3922, unspecified = 266) aged between 16 and 68. years (M= 37.00, SD= 12.09) completed the MTQ48. Model fit was assessed using confirmatory factor analysis (CFA) and exploratory structural equation modeling, in addition to the robust maximum likelihood estimator. Overall, our results support the factorial validity of the MTQ48 and indicate that the MTQ48 is a robust psychometric measure of mental toughness. Along with previous data, which supports the internal validity of the MTQ48 in addition to results of this study, it would appear that the MTQ48 is an acceptable method of assessing mental toughness. © 2012 Elsevier Ltd.
Keywords: General Psychology